Juegos tradicionales como estrategia para mejorar la motricidad gruesa en los niños de preparatoria de la escuela de educación básica “Graciela Felipa Atarihuana” en el período 2019-2020. - Cedeño Ontaneda, Briggette del Cisne (2021)
The research Titled TRADIT IONAL GAMES AS A STRATEGY TO IMPROVE THICK MOTOR IN THE HIGH SCHOOL CHILDREN OF THE BASIC EDUCATION SCHOOL "GRACIELA FELIPA ATARIHUANA" IN THE PERIOD 2019-2020.; The General objective was to determine how traditional games as a strategy improve gross motor skills in high school children. In the literature review, topics related to traditional games and gross motor skills were addressed; In the development of the investigation the methods were used: analytical-s synthetic, inductive-deductive and statistical-descriptive; In order to obtain information, the teacher was interviewed and the children were given the EPP Test (La Cruz y Mazaira Pre-School Psychomotor Assessment Scale), which allowed diagnosing the development of psychomotor skills. The investigated sample comprised between 2 teachers and 18 children. The results obtained in the pre-test reflected that 81% of the children presented difficulties in their psychomotor skills such as balance, leg coordination and body outline. To support gross motor development, a motor activity guide was designed and applied. After the application of the proposal, gross motor development was improved where 97% of those investigated obtained a high and significant level, the results obtained allow us to determine that traditional games undoubtedly help improve gross motor skills, strengthening motor skills in high school children, so teachers should be informed of the use of strategies aimed at developing gross motor skills.